Quantification of florfenicol and its metabolites in fillets of Nile tilapia: Synthesis of metabolites and validation of an on-line solid-phase extraction-ultra high-performance liquid chromatography-tandem mass spectrometry method - Paula Rocha de Queiroga, Anna; Freitas Pereira de Souza, Gabriela [UNESP]; Mateus Assane, Inácio [UNESP]; Messias, Thiago; Pilarski, Fabiana [UNESP]; Schloter, Michael; Gonçalves Salles, Airton; Rath, Susanne (Elsevier, 2024)
This study concerns the synthesis of the florfenicol (FF) metabolites florfenicol amine (FFA), florfenicol alcohol (FFOH), and monochloroflorfenicol (FFCl), for their subsequent use as reference standards in On-line solid-phase extraction-ultra high-performance liquid chromatography-tandem mass spectrometry (SPE-UHPLC-MS/MS) analysis. The metabolites were characterized using 1H and 13C NMR, as well as HRMS, and their purities were confirmed by quantitative NMR to ensure analytical reliability. Validation of the developed analytical method showed that it presented acceptable performance, with linearity >0.99 for all the target analytes, accuracies within ±10 % of nominal concentrations, and intra- and inter-day precisions within 15 %. Application of this method to fillets from fish that had been treated with florfenicol (dose of 10 mg/kg bw daily) demonstrated its effectiveness in consistently detecting FF and its metabolites throughout the treatment. The results emphasized the utility of the method for enhancing pharmacokinetic and residue depletion research. The ability to precisely monitor the drug and its metabolites in treated fish provides important insights into florfenicol metabolism, laying the groundwork for further comprehensive profiling studies of metabolites in fish tissue.
Keywords: Antimicrobial residues; Fish tissue analysis; Florfenicol; Metabolites synthesis; On-line solid-phase extraction-ultra high-performance liquid chromatography-tandem mass spectrometry; QuEChERS